Whistleblowing System dan Lingkungan Pengendalian Dalam Pencegahan Korupsi Dana Desa dimoderasi Perilaku Etis - Kuraini Nur Dinia; Ahmad Rosyid (Jurusan Akuntansi Syariah Fakultas Ekonomi dan Bisnis Islam UIN K.H. Abdurrahman Wahid Pekalongan, 2022)
The increasing number of corruption cases in the village government requires preventive measures to prevent the increase in the number of cases. This research aims to determine the effect of the whistleblowing system and control environment on efforts to prevent corruption in the village government with ethical behavior as moderating. This research is a quantitative research using purposive sampling technique in taking the sample. This study uses primary data by sending questionnaires and secondary data obtained from official sources. From 144 village officials in each village in Blado District, an analysis was carried out using SPSS 26, and using Moderates Regression Analysis as a regression test on the moderating variabel. The test results show that the whistleblowing system and control environment have a significant effect on preventing corruption, and ethical behavior can not moderate the whistleblowing system and control environment for preventing corruption.